Demokrasi dan kapitalisme global pasca perang dingin - Budiawan Budiawan (Universitas Negeri Yogyakarta, 2004)
Democracy do not just measure can take place it general election by prosedural in a state, but core of democracy that is confessing of mirror democracy have to in it. More than that journey and prospect democracy in Indonesia, goodness of level of national and also local there is tendency determined by those who own the capital. Indicator that democracy determined by visible capital owner at legislative institute good process recruitment and also executive. Correct expression to depict the situation